Telesna vadba kot pomemben del celostne obravnave posameznika - model "moč polne angažiranosti" - Šterbucl, Jure (Šport (Ljubljana), 2016)
The main goal of the article is to present a selected model for the overall treatment of an individual person. Initially, we present the well-established "The Power of Full Engagement" model created by James E. Loehr and Jack Groppel The full-engagement model leads a person to act upon planned principles and procedures in line with their personal and business mission, which includes development at four levels: physical, emotional, mental and spiritual. The tasks at individual levels are designed according to the principles of rituals so that users lose minimum time and energy on preparing and organising the procedures. The model is basically intended for businessmen and elite athletes under high mental and emotional loads and, concurrently, lack time and energy. The programme has been verified and established in practice in the USA, whereas use of its versions in Slovenia has enabled the assessment of its applied value in our environment with the help of our own experience and the experience of certain other participants. The model seems suitable and practical, especially the part on physical preparation. Yet the style of the modelćs presentation and some of its results was assessed by the participants as populist, which is why it has to be adjusted to users in Slovenia. The model as such and consideration of the proposed routines can contribute importantly to the high quality lifestyle of people under strong pressures.
Keywords: angažiranost; energija; energy; engagement; management; physical preparation; routines; rutine; sport; šport; telesna priprava; upravljanje